Multi-scale evaluation of a 3D lake model forced by an atmospheric model against standard monitoring data. (May 2021) - Amadori, Marina; Giovannini, Lorenzo; Toffolon, Marco; Piccolroaz, Sebastiano; Zardi, Dino; Bresciani, Mariano; Giardino, Claudia; Luciani, Giulia; Kliphuis, Michael; van Haren, Hans; Dijkstra, Henk A.
Abstract: Evaluating a three-dimensional lake model requires large datasets of many variables, including velocity fields, that are seldom available. Here we discuss how to assess the performance of a model at multiple scales (in time and space) with data from standard monitoring systems, i.e., mostly limited to water temperature. The modeling chain consists of a lake hydrodynamic model (Delft3D-Flow) forced by an atmospheric model (WRF, Weather Research and Forecasting). The two models are tested on the case study of Lake Garda (Italy), where a comprehensive dataset of atmospheric and water temperature observations is available. Results show that a consistent picture of the inherent dynamics can be reproduced from a heterogeneous set of water temperature data, by distilling information across diverse spatial and temporal scales. The choice of the performance metrics and their limitations are discussed, with a focus on the procedures adopted to manage and homogenize data, visualize results and identify sources of error. Highlights: A three-dimensional atmosphere-lake modeling chain is set up. Tested at different spatial and temporal scales against routinely available data. Different metrics and methods to analyze the models' results are discussed. Interannual to sub-daily fluctuations of water temperature show coherent dynamics. Large errors of the lake model can be due to weather forcing inconsistencies.